Institutionalization Of Sport Clubs: Case Study Of Sport Managers - Dağlı Ekmekçi Yeter Aytül (European Scientific Journal, ESJ, 2016)
The place of sport is increasing day by day in our life and therefore to manage institutions well in the sport industry with its sub-sectors is important. Institutionalization process is composed of “formal operations structure”, “formal organizational structure”, “professionalism”, delegation of authority”, “cultural structure”, “compliance with the institutional environment”, “corporate social responsibility”, “compliance with social values and norms”, “transparency and accountability” and “compliance with the formal structure” elements. The aim of this study is to examine the institutionalization of sport clubs, how the managers and workers evaluate their clubs under these 10 elements. The data was collected from 10 managers from Super League and PTT 1. League clubs, which are the top level organizations of Turkish football system. The survey data obtained from the Super League and 1. League clubs managers and interview data by content analysis with the N Vivo9 program were evaluated. As a result, the elements of institutionalization are not completely available in sport clubs in Turkey yet and in addition to this elements providing institutionalization in the literature, “amateur/development level (grass roots)” should be taken into consideration covering its budget, physical plant, psycho-social support etc.